PERCAMPURAN BUDAYA BUGIS DENGAN BUDAYA MELAYU DI DESA PEBENAAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Carles, Yulius; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Bugis an ethnic group with origins in South Sulawesi region. The main characteristics of this ethnic group is the language and customs so that the Malay and Minangkabau migrants who migrated to Sulawesi since the 15th century as an administrative personnel and traders in the Kingdom of Gowa and been acculturated, also categorized as the Bugis. Indonesia based on the 2000 census, the population of the Bugis as many as about six million people. Now the Bugis people also spread in various provinces in Indonesia, such as Southeast Sulawesi, Central Sulawesi, Papua, East Kalimantan, and South Kalimantan. Bugis people are also many who migrated to foreign nationals. Bugis are the tribes who belong to the Deutero Malay tribes. Go to the archipelago after the first wave of migration from mainland Asia rather Yunan. The word "Bugis" comes from the word To Ugi, which means the Bugis. Naming "Ugi" refers to the first king of the Chinese empire contained in Pammana, Wajo today, namely La Sattumpugi. The purpose of the study is to examine the process of entry into Bugis Village Pebenaan, to know the development process in the village Bugis Pebenaan, to know the process of mixing of cultures with Malay culture Bugis Village Pebenaan, to know the result of the mixing of cultures Bugis and Malay culture The village Pebenaan. The method used in this study is the historical method and qualitative methods. Data were obtained from interviews and analyzed in its own language. The research location is in the village of the District Pembenaan Keritang Indragiri Hilir. When the study started from the seminar proposal to the Thesis exam. Data collection techniques used are observation, interview techniques, technical documentation and technical literature. Results from this study is the cultural mix between Bugis with ethnic Malays, while the mix, namely in terms of language, systematic livelihood, systems life equipment, techbnology and kesesnian. Factors that influence the occurrence of the mixing of cultures is due to the similarity of cultural elements, tolerance, social activities.Keywords: Mixing, Culture Bugis, With, Malay2